Various radiological findings in patients with COVID-19: A case series. (February 2021) - Riawati, Theresia; Indrarto, Wikan; Fauzi, Aditya Rifqi; Widitjiarso, William; Gunadi,
Abstract: Introduction: Radiological evaluation of suspected COVID-19 patients is required for early detection of thoracic involvement, particularly in emergency units, while waiting for definitive diagnosis by real-time reverse transcription polymerase chain reaction (RT-PCR). Here, we report a case series of CXR findings in Indonesian patients with COVID-19 in our institution. Presentation of cases: We included 7 patients with COVID-19 confirmed by RT-PCR, including 4 females and 3 males, with ages ranging from 36 to 71 years. All patients showed abnormal findings on CXR when admitted to the hospital, except one, composed of ground glass opacity (GGO) (n = 1), consolidation (n = 3), and both (n = 2). Both and one side of the lung were affected in three and three (left side = 2; right side = 1) patients, respectively. Pneumonia degrees of mild, moderate and severe were observed in three, one, and two patients, respectively. All patients eventually recovered. Discussion: CXR is the most common radiological examination for patients with respiratory disorders, including COVID-19, and it is readily available in almost all health care facilities. The imaging manifestation of COVID-19 is similar to viral pneumonia but also has its own characteristics, including GGO, consolidation, multiple plaque shadows, and interstitial changes that are mostly seen in peripherals and subpleural areas, as well as shadow infiltration in both lungs. Conclusion: CXR showed various abnormality findings in patients with COVID-19, including the type, location, and degree of pneumonia. Moreover, CXR is considered more effective and useful for initial screening and follow-up of the progress of patients with COVID-19. Highlights: CXR is the most common radiological examination for patients with respiratory disorders, including COVID-19. CXR is considered more effective and useful for initial screening and follow-up of the progress of patients with COVID-19. CXR shows various abnormality findings in patients with COVID-19, including the type, location, and degree of pneumonia.